Design and Analysis of a Narrowband Stepped Digital Elliptic Filter at 5 GHz - Svanberg, Hans (My University, 2024)
The increasing frequency and complexity of modern radio frequency (RF) systems makes more compact components essential, particularly in antenna arrays, where numerous electronic components must fit within the small spaces between antenna elements. Filters are a crucial component to every RF system, making the development of more compact filter solutions necessary. Furthermore, new and precise microfabrication methods are emerging where the cost of production is influenced by the physical size of the components. In 1969, a narrowband bandpass filter structure, the stepped digital elliptic filter, was introduced. It has received little to no attention in subsequent research due to difficulties with tuning and fabrication. To the best of the author’s knowledge, this is the most compact higher-order elliptic function bandpass filter structure consisting solely of distributed elements capable of achieving n − 1 transmission zeros. The unique structure also allows the resonators to be suspended without the use of dielectrics, enabling high Q values. Considering advances in microfabrication technology and the need for more compact solutions, it is now an opportune time to revisit this filter structure. Starting from network theory and progressing to electromagnetic simulations, a filter prototype with a fractional bandwidth of 11%, a ripple level of 10%, and a minimum stopband attenuation of 40 dB was designed at 5 GHz, demonstrating close agreement between the simulated and theoretical results, with a return loss above 15 dB in the passband. The filter prototype was shown to be sensitive to fabrication errors, with tolerances greater than 5 μm severely degrading the return loss. Two different designs are proposed suitable for fabrication with the mentioned specifications. In addition, filter characteristics and capacitance matrices (relating directly to the physical dimensions of the filter) for stopband attenuation levels of 30 dB, 40 dB and 60 dB, return losses of 28 dB and 14 dB, and fractional bandwidths (FBW) between 1% and 30% are presented, as well as the structure’s dependence on scaling of the capacitance matrices. Finally, the filter structure has been shown to be suitable for design using microfabrication, with almost any size and filter characteristics with FBWs below 30% possible with sufficiently precise manufacturing tolerances.
Keywords: Filters; Bandpass; Stepped digital elliptic filter